The phase stability of Ni2CrFeMox multi-principal-component alloys with medium configurational entropy. (15th November 2015) - He, Feng; Wang, Zhijun; Zhu, Man; Li, Junjie; Dang, Yingying; Wang, Jincheng
Abstract: The phase stabilities of Ni2 CrFeMox (x = 0.1–0.5) multi-principal-component alloys with medium configurational entropy are investigated through long-time annealing at 600, 750, 900 and 1000 °C respectively. Similar to the high entropy alloy, the solid solution of FCC phase is the main constitute part in the alloys. σ phase shows up in the alloys with higher Mo content. The equilibrium solubility of Mo in the solid solution decreases as the temperature decreases. Pseudo binary phase diagram of (Ni2 CrFe)1 − x Mox is constructed and discussed based on the annealed results. The hardness measurement also illustrates the phase stability of Ni2 CrFeMox alloys. Graphical abstract: The single FCC solid solution phase in the Ni2 CrFeMo0.1 MPCA is stable after annealing at different temperatures, while the alloys with a larger Mo content (x > 0.1) show different behaviors in phase stabilities. When x is smaller than 0.4, the alloys at as-cast state have single FCC solid solution; meanwhile, when the alloys are annealed at different temperatures for a long time, the FCC solid solution is not stable and σ phase occurs when x > 0.1. Highlights: We investigated the phase stability of Ni2 CrFeMox (x = 0.1–0.5) alloys. The Ni2 CrFeMo0.1 alloy shows single FCC structure at all temperatures. When annealed at different temperatures, the FCC phase is unstable when x ≥ 0.2. The highest hardness occurred at an annealing temperature of 750 °C.